A Longitudinal Pilot Study on Cognition and Cerebral Hemodynamics in a Mouse Model of Preeclampsia Superimposed on Hypertension: Looking at Mothers and Their Offspring - Trigiani, Lianne J.; Lecrux, Clotilde; Royea, Jessika; Lavoie, Julie L.; Lesage, Frédéric; Pilote, Louise; Hamel, Edith (Frontiers in Physiology, 2021)
Preeclampsia is a common hypertensive disorder in pregnant women and whose causes and consequences have focused primarily on cardiovascular outcomes on the mother and offspring, often without taking into consideration the possible effects on the brain. One possible cause of preeclampsia has been attributed to alterations in the renin-angiotensin system, which has also been linked to cognitive decline. In this pilot study, we use a mouse model that chronically overexpresses human angiotensinogen and renin (R+A+ mice) that displayed characteristics of preeclampsia such as proteinuria during gestation. Offspring of these mothers as well as from control mothers were also examined. We were primarily interested in detecting whether cognitive deficits were present in the mothers and offspring in the long term and used a spatial learning and memory task as well as an object recognition task at three time points: 3, 8, and 12 months post-partum or post-natal, while measuring blood pressure and performing urine analysis after each time point. While we did not find significant deficits in preeclamptic mothers at the later time points, we did observe negative consequences in the pups of R+A+ mice that coincided with hemodynamic alterations whereby pups had higher whisker-evoked oxygenated hemoglobin levels and increased cerebral blood flow responses compared to control pups. Our study provides validation of this preeclampsia mouse model for future studies to decipher the underlying mechanisms of long-term cognitive deficits found in offspring.